The link between corporate social responsibility disclosure and profitability, in Lithuanian listed companies - Jefimova, Emilija Alenksandra; Kalniūtė, Deimantė; Kolesnik, Gabrielė (Buhalterinės apskaitos teorija ir praktika, 2024)
Disclosure of CSR information can not only makes companies more attractive but also gives them a competitive advantage. Often, engaging in socially responsible activities can lead to increased costs for the company. This paper examines the relationship between corporate social responsibility disclosure and a company's profitability, which can be positive, negative and neutral. The paper presents a methodology for assessing the relationship between corporate social responsibility disclosure and profitability. The study assesses the relationship between corporate social responsibility disclosures and profitability and earnings per share of Lithuanian companies listed on the Nasdaq Baltic Stock Exchange in 2017-2022. The study found that CSR disclosure has no statistically significant relationship with return on assets (ROA), return on equity (ROE) and profitability before interest and tax (EBIT P). However, a positive, very weak statistically significant relationship was found between CSR disclosure and earnings per share (EPS). This may indicate that disclosure of CSR in Lithuanian listed companies increases earnings per share.
Keywords: corporate social responsibility; return on assets; return on equity; earnings per share; EBIT margin